(untitled) (Baltic Journal of Sport and Health Sciences, 2018)
Research deals with the problem what social identifications are characteristic of the higher school students and how they are related to other factors influencing them. Research object was the social identifications of students. Research aim was to characterize the manifestation of social identifications of would-be physical education and sports specialists and to reveal their links with the independent variables of the research. Research participants were 622 1—4 th year students of the Lithuanian Academy of Physical Education, the faculties of Sports Education and Sports Technologies. The social identifications of students were measured using M. Hooper (1976) Social Identification Measurement Scale. The factor analysis of social identifications distinguished five factors. Social identifications typical of would-be specialists of physical education and sports were linked to social prestige (wish to have a well- paid job and be respected in the society), family (the roles of husband / wife, father / mother), age (importance of being adult), nationality (importance of being Lithuanian) and political activity (wish to belong to or support a political party). The distinguished social identifications were related to gender (girls compared to boys want more to be adults, but their national identification is weaker), academic achievements (higher achieving students are more identified with family, and it is more important for them to be adults), sports activities (students higher achieving in sports are more identified with their nationality) and other sociodemographic indicators (better-off students want to be adults more, and national identification is more important to those students whose parents are blue-collar workers and farmers compared to the children of white-collar workers). Keywords: social identifications, higher education, Social Identification Measurement Scale.